Behavioral Health Training to Address the Needs of Adolescents: Outcomes of the GLOBE Youth Program. - Sampson, McClain; Parrish, Danielle E.; Washburn, Micki (Journal of Social Work Education)
This article outlines the outcomes of a specialized master's of social work (MSW) training program on students' (N=96) ability to work effectively in behavioral health care settings with adolescents and transitional age youth from diverse racial, ethnic, and linguistic backgrounds. Program design, curriculum development, and associated activities for the 3-year MSW training program at a large southern urban university are described. The results of this training program were assessed using a one-group pretest–posttest design across three cohorts to assess change with regard to interprofessional competencies, interprofessional attitudes, and cultural competency. Overall, the GLOBE Youth program was associated with increased interprofessional competence and self-reported readiness to work in interprofessional settings with diverse adolescents and transitional age youth experiencing mental health concerns. Implications for social work education and future research in this area are discussed.